Lifestyle medicine. an alternative to the advance of non transmissible diseases (Revista Venezolana de Salud Pública, 2020)
Lifestyle Medicine (MdelEV) has gained relevance in the prevention, treatment and reversal of most chronic diseases, directly addressing its underlying causes. Based on the foregoing, this article aimed to carry out a descriptive review of fundamental elements that characterize Lifestyle Medicine, its advances in clinical research in the areas of nutrition, exercise and stress reduction, as well as the growing trend of make it an integral component of the curricula of medical schools. An exhaustive search was carried out in different documentary sources, using the categories Lifestyle Medicine, basic principles of Lifestyle Medicine, Conventional Medicine vs.. Lifestyle Medicine, clinical studies at MdelEV, as well as lifestyle medicine as a medical subspecialty. Approximately 60 abstract scientific articles were reviewed. Through the use of inclusion criteria, 27 articles were selected and subjected to a comprehensive and analytical reading. In the development and discussion of the subject, the results of the review are presented, highlighting the use of the model of social determinants of health proposed by the WHO, findings of experimental research on the reversal of risk factors in STDs, and advances in training professional. In the discussion they combine the results of all the selected articles with a critical position.
Keywords: Lifestyle Medicine; STDs; risk factors; prevention